GASTROESOPHAGEAL REFLUX DISEASE'S IMPACT ON CHILDREN'S HEALTH - Ana Maria Laura Buga; Anca Adam Raileanu; Anca Lavinia Cianga; Georgiana Scurtu; Tudor Ilie Lazaruc; Laura Stefana Galatanu; Roxana Alexandra Bogos; Dragos Catalin Ghica; Maria Adriana Mocanu (Romanian Society of Oral Rehabilitation, 2023)
Gastroesophageal reflux becomes pathologic when the reflux episodes determine bothering symptoms and or complications. It is a pathology seen both in adults and children; in pediatric patients is a frequent reason for medical visits because of its symptoms that are bothersome both for children and caregivers, especially in infants. Usually, symptoms frequency declines by the age of one year old but when it persists practitioners must intervene with both general measures and medical treatment. The diagnostic is mainly clinical, but when other pathologies that can determine gastroesophageal reflux must pe excluded, imaging methods and esophageal pH measurement can be used.